Reconstruction of Indonesian Arts Education Pedagogy: From Aesthetic Reproduction to Industrialization of Creativity - Ayu Titis Rukmana Sari; Wahyudi; Ardika Dwi Gita Pratama (Universitas Nusantara PGRI Kediri, 2026)
Arts education in Indonesia currently stands at an ideological crossroads between preserving traditional aesthetics and the demands of creative industrialization in the digital economy. This article aims to critically analyze the paradigm of arts education in Indonesia and develop a conceptual framework for pedagogical reconstruction relevant to the challenges of the 21st century. The research employed a qualitative approach using the Critical Conceptual Literature Review (CCLR) method combined with Critical Discourse Analysis (CDA). Data were obtained through a literature search of scientific articles, academic books, and international organization reports relevant to arts education, critical pedagogy, cultural studies, creativity, and the creative industry in Scopus, ERIC, Google Scholar, and Garuda databases. The research identified four main themes shaping the paradigm of arts education in Indonesia: aesthetic reproduction, cultural romanticization, digital transformation, and creative pedagogy. A synthesis of these four themes indicates that arts education remains oriented toward the preservation of artistic forms rather than the development of critical and innovative creativity, thus failing to fully address the needs of the creative community. Based on these findings, this article offers a conceptual framework for reconstructing arts education pedagogy that integrates creativity, critical reflection, cultural contextualization, digital literacy, and collaboration as the foundation of transformative arts education in the creative industry era